Videogames and Therapy: A Narrative Review of Recent Publication and Application to Treatment - Franco, Gilbert E. (Frontiers in Psychology, 2016)
Individuals who play videogames can interact with virtual worlds, resulting in emotional and intellectual connections that have have therapeutic implications in the hands of a skilled and informed therapist. There is research available in the literature that suggests that videogames are a viable option in psychotherapy. The present article provides a review of the literature available in the use of videogames in treatment, discusses the importance of disseminating the findings in the literature, and discusses the integration of videogames in treatment.